Impacts of Wind Stress Changes on the Global Heat Transport, Baroclinic Instability, and the Thermohaline Circulation - Machado, Jeferson Prietsch [UNESP]; Justino, Flavio; Pezzi, Luciano Ponzi (Hindawi, 2016)
The wind stress is a measure of momentum transfer due to the relative motion between the atmosphere and the ocean. This study aims to investigate the anomalous pattern of atmospheric and oceanic circulations due to 50% increase in the wind stress over the equatorial region and the Southern Ocean. In this paper we use a coupled climate model of intermediate complexity (SPEEDO). The results show that the intensification of equatorial wind stress causes a decrease in sea surface temperature in the tropical region due to increased upwelling and evaporative cooling. On the other hand, the intensification of wind stress over the Southern Ocean induces a regional increase in the air and sea surface temperatures which in turn leads to a reduction in Antarctic sea ice thickness. This occurs in association with changes in the global thermohaline circulation strengthening the rate of Antarctic Bottom Water formation and a weakening of the North Atlantic Deep Water. Moreover, changes in the Southern Hemisphere thermal gradient lead to modified atmospheric and oceanic heat transports reducing the storm tracks and baroclinic activity.